DysScreen: A Mobile-Based Application for Screening of Dyslexia for Young Children (Journal of Digital System Development, 2024)
Early identification of dyslexia is crucial for timely intervention to mitigate the disorder's impact on the affected individuals. Despite its prevalence, dyslexia often goes undetected, especially in its early stages, leading to various academic and psychological well-being issues. This paper presents the development and evaluation of DysScreen, a mobile-based application designed for screening dyslexia in children from 4 to 9 years old. The development involved a comprehensive project lifecycle, including planning, requirement gathering, design, and implementation. Essential requirements were identified through questionnaires and a review of the literature and the Paediatric Protocol, creating functional features such as multilingual support, screening test questions, and detailed result reports. The design was visualised using Unified Modeling Language (UML) diagrams to ensure clarity and precision in functionality. Findings from 30 respondents during user testing indicated that DysScreen holds significant potential to aid parents, guardians, and educators in the early detection of dyslexia among the target age group, providing valuable insight for early intervention. This work contributes to the field by offering a scalable and accessible solution to addressing a critical need in dyslexia screening.